Prognostic significance of skin autofluorescence in patients undergoing maintenance hemodialysis - Darya Yu. Konovalova; Petr A. Lebedev; Andrey A. Loginov; Raisa A. Povalyaeva; Dmitriy V. Kornilin; Vladimir N. Grishanov; Marina V. Komarova (КардиоСоматика)
BACKGROUND: Maintenance hemodialysis remains the most common modality of renal replacement therapy, with a consistently high demand. Despite technological advances in recent decades, this high-cost treatment is still associated with a substantial mortality rate. Currently, numerous parameters linked to poor prognosis have been identified, among which skin autofluorescence represents an accessible method for assessing tissue accumulation of glycation end-products (glycotoxins).